Perspectives of Chinese students on studying MA Music programmes in a UK University (Orfeu, 2019)
Continuing interest in higher Music education in the UK from the international market has led to increased recruitment of students from China and Hong Kong; however, academic scholarship focusing on this pedagogical context has not grown as swiftly as student numbers. This qualitative study contributes to literature investigating the complexities of higher Music education as perceived by students from China and Hong Kong undertaking one-year taught Music MA programmes at a UK university. Semi-structured interviews with nine international postgraduate students revealed information about their previous studies in China and Hong Kong, their choice of UK programme, family support, future plans and views on academic and performance study in the different countries. Students discussed the challenges of UK study relating to language skills, critical thinking and the peer group, but also identified expansion of repertoire, individuality in performance, access to a wide range of resources, facilities and opportunities, and the supervisor relationship as positive learning experiences. Findings relating to informed independent thinking, academic and performance teaching, authenticity and agency, and pedagogical potential are of relevance to educators.